Optimization of Hydrogen‐Evolving Photochemical Molecular Devices1. Issue 22 (8th April 2015) - Pfeffer, Michael G.; Kowacs, Tanja; Wächtler, Maria; Guthmuller, Julien; Dietzek, Benjamin; Vos, Johannes G.; Rau, Sven
Abstract A molecular photocatalyst consisting of a RuII photocenter, a tetrapyridophenazine bridging ligand, and a PtX2 (X=Cl or I) moiety as the catalytic center functions as a stable system for light‐driven hydrogen production. The catalytic activity of this photochemical molecular device (PMD) is significantly enhanced by exchanging the terminal chlorides at the Pt center for iodide ligands. Ultrafast transient absorption spectroscopy shows that the intramolecular photophysics are not affected by this change. Additionally, the general catalytic behavior, that is, instant hydrogen formation, a constant turnover frequency, and stability are maintained. Unlike as observed for the Pd analogue, the presence of excess halide does not affect the hydrogen generation capacity of the PMD. The highly improved catalytic efficiency is explained by an increased electron density at the Pt catalytic center, this is confirmed by DFT studies.